2021
DOI: 10.3389/fpsyt.2020.593355
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of Psychotic-Like Symptoms as Measured With the Prodromal Questionnaire, Brief Version (PQ-B) in Adolescent and Adult Population Samples

Abstract: Valid measurement of group differences in self-reported psychotic-like experiences (PLEs) requires knowing any group-specific measurement properties of the instruments. We investigated the measurement invariance of the 21-item Prodromal Questionnaire–Brief (PQ-B) questionnaire across gender, ethnic minority/majority status, and presence of depressive symptoms in two different US non-clinical undergraduate samples (N = 1,099). For each item, endorsement of the experience and the associated distress were combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
0
14
1
1
Order By: Relevance
“…However, the PQ-B Distress scale displayed configural, metric, and scalar invariance in the current study across almost all indicators (with the exception of the McD for four of the 11 analyses). Previous studies have relatively consistently found that the PQ-B Distress scores lack complete scalar invariance across groups Lång et al, 2020). Given that the finding of scalar invariance was somewhat equivocal for the PQ-B Distress analyses and is inconsistent with previous research, this finding should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, the PQ-B Distress scale displayed configural, metric, and scalar invariance in the current study across almost all indicators (with the exception of the McD for four of the 11 analyses). Previous studies have relatively consistently found that the PQ-B Distress scores lack complete scalar invariance across groups Lång et al, 2020). Given that the finding of scalar invariance was somewhat equivocal for the PQ-B Distress analyses and is inconsistent with previous research, this finding should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 61%
“…In the current study, there were too few Asian and Multiracial participants to form groups in the multigroup measurement invariance analyses. Similarly, other research has found a lack of complete measurement invariance with race defined as two groups including a White and a minority group (Lång et al, 2020). A measurement invariance analysis of an adapted version of the scale, the Prodromal Questionnaire Brief Child version (PQ-BC), with data from the Adolescent Brain and Cognitive Development study included a similar conceptualization of race/ethnicity (i.e., White, African-American, Hispanic, and Other) and also found that the PQ-BC had scalar invariance across race and sex (Karcher et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…RIDEP • Nº67 • Vol.1 • 87-99 • 2023 pesar de ser una muestra clínica que contó con un número significativo de participantes, ésta no representa a toda la población de pacientes diagnosticados con Esquizofrenia en Chile. Por otro lado, la muestra de participantes contiene un número significativo de participantes que se identifican con alguna etnia (Especialmente la etnia Aymara), por lo que siguiendo los trabajos de invariancia métrica en trastornos psicóticos de Lång et al (2021), en éste estudio no se contrastó el supuesto de invariancia métrica considerando la etnia y el sexo. Futuras investigaciones debiesen considerar análisis de invarianza de la escala RAS-18 para garantizar la equivalencia de las medidas en diferentes poblaciones, de modo que se puedan realizar evaluaciones precisas para informar los esfuerzos de intervención y tratamiento en la esquizofrenia tomando en cuenta variables como la etnia de los participantes y la inclusión de la cultura de pueblos originarios de la región.…”
Section: Discussionunclassified
“…examined the measurement invariance of the PQ-B, both in undergraduate samples (Cicero et al, 2019;Lång et al, 2021). Nevertheless, this pattern holds across different races, ethnicities, countries, and language translations of the scales.…”
Section: Measurement Invariance Of Psychosis Scalesmentioning
confidence: 97%
“…These and other screening scales have been shown to lack complete scalar invariance among minority groups (i.e., item responses differ based on group membership rather than latent level of psychosis) in nearly every study that has examined the issue (e.g., Cicero, 2016; Cicero et al, 2019; Fonseca-Pedrero et al, 2018; Li et al, 2020; Ortuño-Sierra et al, 2013). However, to our knowledge, no studies have examined the measurement invariance of the YPARQ and only two studies have examined the measurement invariance of the PQ-B, both in undergraduate samples (Cicero et al, 2019; Lång et al, 2021). Nevertheless, this pattern holds across different races, ethnicities, countries, and language translations of the scales.…”
Section: Psychosis In Hispanic Individualsmentioning
confidence: 99%